Acculturation of Galician Jews in Bosnia – officials’ portfolio analysis - Maleszka, Mateusz (Balcanica Posnaniensia. Acta et studia, 2016)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The Archives of Bosnia-Herzegovina, marked with tragedy of fire, had stored large archive collections of files of Austro-Hungarian officials. Among them there had been a numerous group of files of Galician officials, including those of Jewish descent (20%). The collection of 19 files that has survived the fire does not entitle us to unequivocally state any thesis on processes of acculturation of Galician Jews in Bosnia. Nevertheless, we can observe that many Ashkenazi newcomers from Galicia described themselves as Poles, even though initially they had not identified with Polish national idea. Possibly the reason for this is the fact that the Polish community in Bosnia was culturally closer to Galician Jews than local Sephardic population or Ashkenazi immigrants from other countries.